Social Interaction Patterns of Muslim-Hindu in Kampung Loloan, Jembrana: A Sociological-Historical Review - Sarjana, I Putu; Anshori, Yahya (Jurnal Penelitian Agama Hindu, 2023)
Bali has been a model of unique multicultural life, including inter-religious harmony. This study aimed to describe the social interaction of Muslim-Hindu in Kampung Loloan, Jembrana Bali. The type of study was qualitative research, where research data was obtained through literature review, observation, and interviews with Balinese cultural observers and community leaders of Kampung Loloan. The results showed that from the Dutch colonial era (17th century) until the post-reform era, social interaction between Muslims and Hindus in Kampung Loloan experienced ups and downs. In general, social interaction could be sorted into four patterns: (1) social interaction based on kinship (menyamebraya); (2) social interaction based on partnership; (3) social interaction based on the spirit of competition; (4) social interaction based on prejudice. The first, second, and third patterns of social interaction could support the Ajeg Bali movement and the multiculturalism development that strengthened the Unitary State of the Republic of Indonesia (NKRI). Meanwhile, the fourth pattern of social interaction was a latent danger that needed to be anticipated because it could ignite social conflict and reduce national integration.